On the mechanism of gas adsorption for pristine, defective and functionalized graphene. Issue 8 (13th February 2017) - You, Y.; Deng, J.; Tan, X.; Gorjizadeh, N.; Yoshimura, M.; Smith, S. C.; Sahajwalla, V.; Joshi, R. K.
Abstract : Defects are no longer deemed an adverse aspect of graphene. Abstract : Defects are no longer deemed an adverse aspect of graphene. Contrarily, they can pave ways of extending the applicability of graphene. Herein, we discuss the effects of three types of defects in graphene including carbon deficiency, adatom (single Fe) dopants and the introduction of functional groups (carbonyl, ether group) on the NO2 gas adsorption via density functional theory methods. We have observed that introducing Fe on graphene can enhance the NO2 adsorption process. Adsorption energy calculations suggest that the enhancement in NO2 adsorption is more profound for Fe-doped mono- and tetra-vacant graphene than that for Fe doped bi- and tri-vacant graphene, which is favourable for NO2 gas capture applications. The unsaturated carbons in defected graphene as well as the oxygenated functional groups are very active to attract NO2 molecules. However, though the gas binding strength was not as high as the that found in the Fe-doped graphene structure, the relatively low NO2 gas adsorption energy is suitable for the practical gas sensors both for gas sensitivity and the sensor recovery rate factor. This theoretical study can potentially be useful for developing adsorption-based applications of graphene.